Failure of Therapeutic Anticoagulation in COVID-19 Patients With Acute Ischemic Stroke. A Retrospective Multicenter Study - Janes, Francesco; Gigli, Gian Luigi; Kuris, Fedra; Morassi, Mauro; Costa, Paolo; Nesi, Lorenzo; Giacomello, Roberta; Mazzacane, Federico; Leuci, Eleonora; Cavallini, Anna; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Background Acute ischemic stroke (AIS) is a possible complication of coronavirus disease 2019 (COVID-19) infection. Although peculiar clinical features and underlying specific mechanisms of thrombogenesis have been suggested so far, there is no consensus on the appropriate vascular preventive drug regimen in patients with COVID-19. Aim and Methods From a larger clinical series of consecutive acute ischemic strokes related to COVID-19 admitted to three cerebrovascular units in Northern Italy, herein, we describe the clinical features of a subgroup of patients in whom stroke occurred despite therapeutic anticoagulation. Results A total of seventeen/80 AIS related to COVID-19 (21.2%) occurred in anticoagulated patients. Although no blood level was available for Direct Oral AntiCoagulant, the drug dosage was appropriate according to guidelines. Their National Institute of Health Stroke Scale (NIHSS) at admission was 12.0 (SD = 7.4) and 58.8% of them had evidence of large vessel occlusion. The case fatality rate was as high as 64.7%. Discussion and Conclusions The occurrence of an anticoagulation failure seems to be increased in the setting of COVID-19 infection, with worse clinical outcomes if compared to non-COVID-19 related ischemic strokes. We discuss the diagnostic and therapeutic implications of such evidence, suggesting that some arterial thrombotic complications might be either resistant to or independent of the anticoagulation effect.